1988
DOI: 10.1002/ajmg.1320310308
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial and terminal deletions of the long arm of chromosome 4: Further delineation of phenotypes

Abstract: We reviewed 45 patients with a deletion of the long arm of chromosome 4. Forty-one were previous reports (25 terminal deletions and 16 interstitial deletions) and 4 are new cases with terminal deletions. Of the 29 patients with terminal deletions, 18 with deletion at 4q31 and 4 at 4q32----qter had an identifiable phenotype consisting of abnormal skull shape, hypertelorism, cleft palate, apparently low-set abnormal pinnae, short nose with abnormal bridge, virtually pathognomonic pointed fifth finger and nail, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
111
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(113 citation statements)
references
References 25 publications
2
111
0
Order By: Relevance
“…The reported terminal 4q deletions mostly involved breakpoints at 4q31 (22 patients) [4, 5, 6, 7, 8], 4q32 (4 patients) [5, 9], 4q33 (12 patients) [10, 11, 12]and 4q34 (5 patients) [4, 5, 13]. Most interstitial deletions of the long arm of the chromosome 4 involve the q11–q31 segments.…”
Section: Discussionmentioning
confidence: 99%
“…The reported terminal 4q deletions mostly involved breakpoints at 4q31 (22 patients) [4, 5, 6, 7, 8], 4q32 (4 patients) [5, 9], 4q33 (12 patients) [10, 11, 12]and 4q34 (5 patients) [4, 5, 13]. Most interstitial deletions of the long arm of the chromosome 4 involve the q11–q31 segments.…”
Section: Discussionmentioning
confidence: 99%
“…In order to establish a genotype-phenotype correlation, the severity of the phenotype is correlated with the size of the deletion. Thus, several reports suggested that small terminal, or interstitial, distal Cr4q del involving bands 4q34 and 4q35 seems to have little clinical impact, consisting in little facial dysmorphism and mild, or absent, intellectual disability (ID) 4 , and Yakut et al 5 reported a case of a familial interstitial 4q35 deletion with no discernible phenotypic effects. On the other hand, a relatively constant phenotype can be recognised in 4q31 to qter deletion.…”
Section: Introductionmentioning
confidence: 99%
“…1,14,15 In particular, there appears to be a karyotypephenotype correlation because CVM has been noted in almost two thirds of patients with the terminal deletions at 4q31, whereas only about a quarter of patients with the more distal deletions at 4q34 or q35 have CVM. It has been postulated that genes distal to 4q34 may play a critical role in producing a CVM, 14 though the molecular basis is unknown.…”
mentioning
confidence: 99%
“…Over the past 30 years, 50 cases have been reported, 23 (41%) of which have had a cardiovascular malformation (CVM). [1][2][3][4][5][6][7][8][9][10][11][12][13][14] Compared with the 10% frequency in the Baltimore-Washington Infant Study, a case-control study of liveborn infants with a confirmed CVM in 1981-1989, 14 right ventricular outflow tract obstructive defects are more common (35%) in patients with 4q deletion.…”
mentioning
confidence: 99%